В. И. Икскуль фон Гилленбанд. Из пережитого в 1918 году. [Varvara Uexküll von Gyllenband. My Ordeals in 1918] - Okhotin, Nikita; Salman, Marina (Slavica Revalensia, 2022)
This is the first publication in toto of a forgotten memoir “My Ordeals in 1918” by baroness Varvara Uexküll von Gyllenband’s. Originally written in 1919, three years prior to her fleeing Petrograd, the memoir tells the story of her three-week detention by the Bolshevik secret police (the Cheka) in 1918.